Folate-mediated mitochondrial targeting with doxorubicin-polyrotaxane nanoparticles overcomes multidrug resistance - Wang, He (Oncotarget, 2014)
Resistance to treatment with anticancer drugs is a significant obstacle and a fundamental cause of therapeutic failure in cancer therapy. Functional doxorubicin (DOX) nanoparticles for targeted delivery of the classical cytotoxic anticancer drug DOX to tumor cells, using folate-terminated polyrotaxanes along with dequalinium, have been developed and proven to overcome this resistance due to specific molecular features, including a size of approximately 101 nm, a zeta potential of 3.25 mV and drug-loading content of 18%. Compared with free DOX, DOX hydrochloride, DOX nanoparticles, and targeted DOX nanoparticles, the functional DOX nanoparticles exhibited the strongest anticancer efficacy in vitro and in the drug-resistant MCF-7/ Adr (DOX) xenograft tumor model. More specifically, the nanoparticles significantly increased the intracellular uptake of DOX, selectively accumulating in mitochondria and the endoplasmic reticulum after treatment, with release of cytochrome C as a result. Furthermore, the caspase-9 and caspase-3 cascade was activated by the functional DOX nanoparticles through upregulation of the pro-apoptotic proteins Bax and Bid and suppression of the antiapoptotic protein Bcl-2, thereby enhancing apoptosis by acting on the mitochondrial signaling pathways. In conclusion, functional DOX nanoparticles may provide a strategy for increasing the solubility of DOX and overcoming multidrug-resistant cancers.